Q. 1 J4.2( 13 Votes )

# Find the errors and correct the following mathematical sentences

Substitute x = – 3 in

(a) x^{2} + 7x + 12 = (–3)^{2} + 7 (–3) + 12 = 9 + 4 + 12 = 25

Answer :

If LHS is

x^{2} + 7x + 12

Then RHS would be

⇒ x^{2} + 7x + 12

Putting x = (-3)

= (–3)^{2} + 7 (–3) + 12

= 9 + (-21) + 12

= 21-21

= 0

The error is (-21) instead of 4 and end result 0 instead of 25

Hence putting x = (-3) in x^{2} + 7x + 12 results to 0

Rate this question :

Find the errors and correct the following mathematical sentences

(2a + 3)^{2} = 2a^{2} + 6a + 9

Find the errors and correct the following mathematical sentences

(2x)^{2} + 5x = 4x + 5x = 9x

Find the errors and correct the following mathematical sentences

Substitute x = – 3 in

(b) x^{2}– 5x + 6 = (–3)^{2} –5 (–3) + 6 = 9 – 15 + 6 = 0

Find the errors and correct the following mathematical sentences

(x – 4)^{2} = x^{2} – 16

Find the errors and correct the following mathematical sentences

4p + 3p + 2p + p – 9p = 0

AP - Mathematics